2016
DOI: 10.1186/s12879-016-1431-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Candida species in patients with orogastric cancer: susceptibility to antifungal drugs, attributes of virulence in vitro and immune response phenotype

Abstract: BackgroundBecause of the inherent immunosuppression of cancer patients opportunistic infections by Candida spp, occur frequently. This study aimed to identify Candida species in the oral mucosa of 59 patients with orogastric cancer (OGC) and to analyze the immunological phenotype of these patients.MethodsThe yeasts were identified by MALDI-TOF mass spectrometry (MS). For all isolates, we performed phospholipases and proteinases assays, in vitro adherence to buccal epithelial cells (BEC), minimum inhibitory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…It is important to understand the possible role that Candida infection plays in malignant transformation of OLP; studies should report if patients undergo chronic antimycotic therapy considering that pharmacological immunosuppression contributes to overinfection (Lodi et al., ). It would be important to know what kind of Candida is present, as some species are more likely to favor cancer; eventually, it should be considered whether or not the development of drug resistance to Candida can somehow affect the OLP evolution (de Sousa et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand the possible role that Candida infection plays in malignant transformation of OLP; studies should report if patients undergo chronic antimycotic therapy considering that pharmacological immunosuppression contributes to overinfection (Lodi et al., ). It would be important to know what kind of Candida is present, as some species are more likely to favor cancer; eventually, it should be considered whether or not the development of drug resistance to Candida can somehow affect the OLP evolution (de Sousa et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Fungal infections caused by Candida species are common in immunocompromised patients, and the incidence has dramatically increased during the last decades [ 27 , 28 ]. Several virulence factors contribute to the pathogenicity of Candida yeasts, which is one of the main causes of systemic infection in individuals with cancer and contribute to high mortality rates of these patients [ 29 ]. Previous studies reported an incidence of oral yeast colonization and infection amongst cancer patients, ranging from 43% to 90% and 13% to 52%, respectively, depending greatly on the type of cancer, regimens to manage the Candida infections, and advance of the disease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors found C. albicans (74%) species followed by C. glabrata (11.5%), C. tropicalis (2.6%), C. krusei (2.6%) and C. parapsilosis (1.9%) to be involved [ 6 ]. Another study showed that approximately 85% ( n = 50) of cancer patients were positive for culture of Candida species from the oral mucosa, with C. albicans being the most prevalent species, followed by C. glabrata with 14.5% of cancer patients [ 29 ]. Unlike other reports, the uncommon species of S. capitata and P. kluyveri were found to be involved in oral colonization and infection in the current study (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10 microbial isolates comprising of Gram-positive bacteria ( Staphylococcus aureus , Bacillus subtilis ), Gram-negative bacteria ( Escherichia coli , Pseudomonas aeruginosa , Klebsiella pneumoniae ), yeast ( Candida albicans ) and dermatophytic pathogens ( Trichophyton schoenleinii, Trichophyton mentagrophytes, Microsporum gypseum, and Microsporum ferugineum ), previously collected from clinical samples in the postgraduate laboratory of the Department of Pharmaceutical Microbiology and Biotechnology, Faculty of Pharmaceutical Sciences, Nnamdi Azikiwe University, were used in this study. Each of the collected isolates was re-identified and confirmed using the standard protocols as described in the literature [ [19] , [20] , [21] , [22] , [23] , [24] , [25] ].…”
Section: Methodsmentioning
confidence: 99%